The importance of time in nutrient regulation: a case study with spotted-wing Drosophila (Drosophila suzukii) - Deans, Carrie; Hutchison, William (Frontiers in Insect Science, 2023)
Introduction The ability of living organisms to acquire the nutrients needed to carry out required physiological functions has important consequences for fitness. However, an organism must not simply meet the requirements for individual nutrients, but must ingest an optimal balance of multiple nutrients. Despite this, animals rarely consume truly balanced resources, and instead commonly feed selectively across multiple unbalanced resources to reach an optimal balance, i.e., intake target. Nutritional research has predominantly focused on the behavioral strategies employed during nutrient regulation, as well as the fitness consequence of failing to meet intake targets, but little work has been done on the temporal aspects of this process. For instance, within what timeframe must organisms reach their intake target before a fitness cost is incurred? Hours, days, weeks? Methods In this study, we investigated how nutrient regulation interval impacts consumption and performance in adult female spotted-wing Drosophila (Drosophila suzukii). Females were constrained to either a protein- orcarbohydrate-biased diet over different time intervals and at different schedules, while control flies were constrained to one diet for the entire feeding period. Results Regulation interval had a significant impact on feeding behavior and consumption. Total consumption was highest on the shorter interval treatments, where diets were alternated more frequently, and declined as the interval period increased. The relative consumption of both diets was statistically-different across intervals and was higher for the carbohydrate-biased diet. Consumption of the protein-biased diet was more variable across intervals and was more strongly impacted by the daily timing of diet switches. Performance data showed that shorter regulation intervals led to longer fly lifespans, a result commonly observed in studies exploring the impacts of diet macronutrient ratio variability on performance. Discussion These results show that the temporal aspects of nutrition, such as feeding intervals and the timing of resource availability, can have strong impacts on feeding behavior, nutrient regulation, and fitness. These results provide an insight into how consumers may deal with changes in host phenology, the availability of hosts, and changes in nutrient availability within hosts. Understanding these mechanisms will be important for predicting responses to changes in nutrient cycling and resource availability mediated by natural and anthropogenic habitat modifications, such as global climate change.